Compound content analysis apparatus, compound content analysis method, and cell for compound content analysis
Patent Information
- Application Number
- JP2023136891
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0007】 本発明によれば、含有量算出ユニットが、第1電極と第2電極との間に予め設定された電圧を印加したときに第1電極と第2電極との間を流れる電流の電流値の時間積分を実行することにより測定対象溶液中に含まれる測定対象の化合物イオンの含有量を算出する。これにより、測定対象の化合物イオンの価数が判れば、測定対象の化合物イオンの含有量を直接的に求めることができる。従って、標準溶液を使用した検量線の作成が不要となるので、その分、化合物の溶液中に含まれる化合物の含有量を簡単に測定することができる。
Smart Images

Figure 2025030979000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a compound content analyzing device, a compound content analyzing method, and a compound content analyzing cell. [Background technology]
[0002] A method for measuring the content of a compound contained in an aqueous dispersion of the compound by liquid chromatography mass spectrometry has been proposed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2020 / 213691 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the measurement method described in Patent Document 1 requires the creation of a calibration curve using a standard solution, which may make the measurement time-consuming.
[0005] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a compound content analysis device, a compound content analysis method, and a compound content analysis cell that can easily measure the content of a compound contained in a compound solution. [Means for solving the problem]
[0006] In order to achieve the above object, the compound content analyzer according to the present invention comprises: A first electrode; a second electrode disposed opposite the first electrode; a flow path member that is sheet-like and penetrates in a thickness direction, and has a flow path formed therein in which a measurement target solution containing a measurement target compound ion is filled, and one surface side of the flow path in the thickness direction is covered with the first electrode; a charge transfer liquid film that contains a charge transfer liquid and covers the other surface side of the flow path in the thickness direction of the flow path member; a conductive polymer film that contains a conductive polymer and is interposed between the second electrode and the charge transfer liquid film; and a content calculation unit that calculates the content of the compound ion to be measured contained in the solution to be measured by performing a time integration of a current value of a current flowing between the first electrode and the second electrode when a preset voltage is applied between the first electrode and the second electrode. Effect of the Invention
[0007] According to the present invention, the content calculation unit calculates the content of the compound ion of the object to be measured contained in the solution to be measured by performing time integration of the current value of the current flowing between the first electrode and the second electrode when a preset voltage is applied between the first electrode and the second electrode. As a result, if the valence of the compound ion of the object to be measured is known, the content of the compound ion of the object to be measured can be directly obtained. Therefore, since it is not necessary to create a calibration curve using a standard solution, the content of the compound contained in the compound solution can be easily measured. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1A is a schematic diagram of a compound content analyzing device according to an embodiment of the present invention, and FIG. 1B is an exploded perspective view showing the structure of a compound content analyzing cell according to the embodiment. [Diagram 2] 3 is an explanatory diagram of the operation of the compound content analyzer according to the embodiment; FIG. [Diagram 3] FIG. 1 shows a cyclic voltammogram according to Example 1, (A-2) shows a cyclic voltammogram according to Example 2, (A-3) shows a cyclic voltammogram according to Example 3, (A-4) shows a cyclic voltammogram according to Example 4, and (B) shows the PFHxS concentration dependence of peak current values according to Examples 1 to 4. [Figure 4]FIG. 13 is a diagram showing a time profile of a current value according to the fifth embodiment. [Diagram 5] FIG. 13A shows a cyclic voltammogram according to Example 6, and FIG. 13B shows a time profile of the current value according to Example 6. [Figure 6] FIG. 13 is a diagram showing the potential dependence of electrolysis efficiency in Example 6. [Figure 7] FIG. 13 is a diagram showing the flow rate dependency of electrolysis efficiency in Example 7. [Figure 8] FIG. 13A is a graph showing the PFHxS concentration dependence of electrolysis efficiency in Example 8, and FIG. 13B is an enlarged view of a portion of FIG. [Figure 9] 13 is a scatter plot showing the correlation between the theoretical value of the PFHxS concentration in a PFHxS solution and the measured value of the PFHxS concentration in the PFHxS solution obtained by the method of Example 8. [Figure 10] 13 is a cyclic voltammogram according to Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, a compound content measuring device according to an embodiment of the present invention will be described with reference to the drawings. The compound content measuring device according to the present embodiment includes a compound content analyzing cell and a content calculating unit. The compound content analyzing cell includes a first electrode containing Ag ions and Cl ions, a second electrode arranged opposite to the first electrode, a sheet-shaped flow path penetrating in the thickness direction and filled with a solution containing the compound ions of the measurement target, and a flow path member having one side of the flow path in the thickness direction covered with the first electrode, a charge transfer liquid film containing a charge transfer liquid and covering the other side of the flow path in the thickness direction of the flow path member, and a conductive polymer film containing a conductive polymer and interposed between the second electrode and the charge transfer liquid film. The content calculating unit calculates the content of the compound ions of the measurement target contained in the solution to be measured by performing time integration of the current value of the current flowing between the first electrode and the second electrode when a preset voltage is applied between the first electrode and the second electrode.
[0010] As shown in FIG. 1(A), the compound content measuring device according to the present embodiment includes a compound content analyzing cell 1, an injector 2, a voltage source 3, a voltmeter 41, an ammeter 42, and a content calculating unit 5. The injector 2 is equipped with a pump (not shown) for causing a measurement target solution containing a measurement target compound ion introduced into the injector 2 to flow into the compound content analyzing cell 1 at a preset flow rate. The measurement target solution may be a solution containing ions of perfluoroalkyl compounds such as perfluorohexanesulfonic acid (PFHxS), perfluorooctane sulfonic acid (PFOS), and perfluorooctanoic acid (PFOA), and polyfluoroalkyl compounds. Here, the concentration of the measurement target compound ion in the measurement target solution is preferably 5 μM or more and 200 μM or less.
[0011] As shown in FIG. 1(B), the compound content analysis cell 1 includes a first electrode 12 of a metal substrate and a sheet-like second electrode 16 arranged opposite the first electrode 12. Here, the first electrode 12 has a structure in which the surface of a silver (Ag) substrate is covered with silver chloride (AgCl). The second electrode 16 is a sheet-like electrode made of paste-like carbon (C). In addition, the first electrode 12 is provided with through-holes 12a and 12b that penetrate the first electrode 12 in the thickness direction and through which the above-mentioned measurement target solution flows.
[0012] The compound content analysis cell 1 includes a flow path member 13 having a long flow path 13a formed therein, the flow path member 13 being in a sheet shape and penetrating the thickness direction and extending in a direction perpendicular to the thickness direction, a sheet-like charge transfer liquid film 14 containing a charge transfer liquid, and a long sheet-like conductive polymer film 15 containing a conductive polymer and interposed between a second electrode 16 and the charge transfer liquid film 14. The flow path 13a of the flow path member 13 is filled with a solution to be measured, and one side of the flow path 13a in the thickness direction of the flow path member 13 is covered with a first electrode 12. Here, both ends of the flow path 13a in the longitudinal direction face the through holes 12a and 12b of the first electrode 12, respectively. The charge transfer liquid film 14 is a porous film formed in a sheet shape from polytetrafluoroethylene (PTFE) impregnated with a charge transfer liquid, and is arranged so as to cover the other side of the flow path 13a in the thickness direction of the flow path member 13. The charge transfer liquid may be an organic solvent that forms an interface with the aqueous phase to which a hydrophobic salt has been added. For example, the organic solvent may be a halogen-containing solvent such as 2-nitrophenyloctyl ether (NPOE), dichloroethane, or trichloromethane, an ether solvent such as diethyl ether or tetrahydrofuran, an aromatic solvent such as nitrobenzene or toluene, or an alkane solvent such as hexane. The hydrophobic salt may be a hydrophobic salt consisting of a hydrophobic cation such as quaternary ammonium, tetraphenylphosphonium, alkylphosphonium, or imidazolium, and a hydrophobic anion such as a halogenated tetraphenyl borate or various sulfonyl imides. The charge transfer liquid may be a hydrophobic ionic liquid such as an asymmetric alkylammonium bis(nonafluorobutanesulfonyl)imide. The conductive polymer film 15 is formed from a paste containing a conductive polymer into a long sheet shape, and is disposed at a position facing the flow path 13a of the flow path member 13. The conductive polymer may be, for example, a polythiophene-based conductive polymer such as poly(3,4-ethylenedioxythiophene), bis(polyethylene glycol) (PEDOT-PEG) to which a hydrophobic anion has been added. The hydrophobic anion may be, for example, a halogenated tetraphenyl borate, various sulfonylimides, or tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (TEPB).The conductive polymer film 15 also contains acetylene carbon black (AB) as a conductive assistant and polyvinylidene fluoride (PVDF) as a binder. When the conductive polymer film 15 contains PEDOT-PEG:TEPB, the content of PEDOT-PEG:TEPB is preferably 5 wt % or more.
[0013] Furthermore, the compound content analyzing cell 1 includes a support member 11 having a plate-shaped first sub-support member 111 arranged on the side of the first electrode 12 opposite to the second electrode 16 side, and a plate-shaped second sub-support member 112 arranged on the side of the second electrode 16 opposite to the first electrode 12 side. The first sub-support member 111 is provided with through holes 111a and 111b penetrating the first sub-support member 111 in its thickness direction, through which the measurement target solution flows. The through holes 111a and 111b are provided at positions overlapping with the through holes 12a and 12b of the first electrode 12 in the arrangement direction of the first sub-support member 111 and the first electrode 12 when the first sub-support member 111 is superimposed on the first electrode 12.
[0014] 1A, the measurement target solution introduced into the injector 2 is pumped into the through-hole 111a of the first sub-support member 111, as indicated by the arrow AR1, and passes through the through-hole 12a of the first electrode 12 and flows into the flow path 13a, as indicated by the arrow AR2. The measurement target solution that has flowed into the flow path 13a then passes through the through-hole 12b of the first electrode 12 and the through-hole 111b of the first sub-support member 111, as indicated by the arrow AR3, and flows out of the compound content analytical cell 1, as indicated by the arrow AR4.
[0015] The voltage source 3 applies a DC voltage between the first electrode 12 and the second electrode 16. The voltage source 3 also has a function of changing the potential of the first electrode 12 with respect to the second electrode 16, which is a reference electrode, from a first potential to a second potential, or from the second potential to the first potential at a preset increase or decrease rate. Here, the first potential is set to, for example, −6.0 V, the second potential is set to, for example, 0.05 V, and the increase and decrease rates are set to, for example, 20 mV / sec. The voltmeter 41 measures the voltage applied between the first electrode 12 and the second electrode 16, and outputs a voltage value signal indicating the measured voltage value to the content calculation unit 5. The ammeter 42 measures the current value of the current flowing between the first electrode 12 and the second electrode 16, and outputs a current value signal indicating the measured current value to the content calculation unit 5.
[0016] The content calculation unit 5 has, for example, a processing device that executes arithmetic processing, and calculates the content of the compound ion of the measurement target contained in the measurement target solution by performing time integration of the current value of the current flowing between the first electrode 12 and the second electrode 16 when a preset voltage is applied between the first electrode 12 and the second electrode 16. The content calculation unit 5 continuously acquires the current value signal input from the ammeter 42 for a preset acquisition time while the potential of the first electrode 12 relative to the second electrode 16 is maintained at a preset target potential. Here, the content calculation unit 5 controls the voltage source 3 based on the voltage value indicated by the voltage value signal input from the voltmeter 41 so that the potential of the second electrode 16 relative to the first electrode 12 is maintained at the aforementioned target potential. This target potential is preferably a voltage more negative than -0.3V. The content calculation unit 5 then calculates the content of the compound ion of the measurement target based on Faraday's second law from the integral value obtained by time integration of the current value indicated by the current value signal acquired during the aforementioned acquisition time. Specifically, the content calculation unit 5 calculates the content of the compound ion by dividing the above-mentioned integral value by the ion valence and Faraday constant of the compound ion.
[0017] Next, the operation principle of the compound content analyzer according to the present embodiment will be described with reference to Fig. 2. When the flow path 13a is filled with the solution to be measured, if a voltage is applied so that the first electrode 12 has a negative potential with respect to the second electrode 16, Ag present at the first electrode 12 is dissolved in water. + is reduced to Cl - The ions move into the measurement target solution W in the flow channel 13a. Accordingly, compound ions (target ions) in the measurement target solution W move into the charge transfer liquid film 14. At this time, the conductive polymer is oxidized, and the TFPB contained in the charge transfer liquid film 14 is oxidized. - moves to the conductive polymer film 15. As a result, a current flows from the first electrode 12 to the second electrode 16. Then, the current value of the generated current is measured by the ammeter 42, and the content of the compound ion in the measurement target solution is calculated from the measured current value.
[0018] As described above, according to the compound content analyzer of this embodiment, the content calculation unit 5 calculates the content of the compound ion of the measurement target contained in the measurement target solution by performing time integration of the current value of the current flowing between the first electrode 12 and the second electrode 16 when a preset voltage is applied between the first electrode 12 and the second electrode 16 of the compound content analysis cell 1. As a result, if the valence of the compound ion of the measurement target is known, the content of the compound ion of the measurement target can be directly obtained. Therefore, since it is not necessary to create a calibration curve using a standard solution, the content of the compound contained in the compound solution can be easily measured.
[0019] Although the embodiment of the present invention has been described above, the present invention is not limited to these. The present invention includes appropriate combinations of the embodiment and the modified examples, and appropriate modifications thereto. EXAMPLES
[0020] The present invention will be specifically described below based on Examples 1 to 9.
[0021] The compound content analysis cells according to Examples 1 to 9 all have the same structure as the compound content analysis cell 1 described in the embodiment. The thickness of the flow path member according to Examples 1 to 9 is 50 μm, and the width and length of the flow path are all 1 mm and 19 mm. The thickness of the charge transfer liquid film according to Examples 1 to 9 is 30 μm, and the charge transfer liquid contained in the charge transfer liquid film is TFPB. - The conductive polymer films according to Examples 1 to 9 were prepared by dissolving PEDOT-PEG:TFPB, AB, and PVDF in an organic solvent, 1-methyl-2-pyrrolidone (NMP), screen printing the solution on the second electrode, and then leaving the solution in a vacuum dryer at 80° C. for 2 hours.
[0022] The compound content analysis cells according to Examples 1 to 4 have different weight ratios of PEDOT-PEG:TFPB, AB contained in the conductive polymer film. The weight ratios of PEDOT-PEG:TFPB, AB, PVDF contained in the conductive polymer film of the compound content analysis cells according to Examples 1 to 4 are shown in Table 1 below.
[0023] [Table 1]
[0024] Using the compound content analysis cells according to Examples 1 to 4, cyclic voltammograms were measured while the flow path of the flow path member was filled with each of the measurement target solutions containing PFHxS at 20 μM, 50 μM, 100 μM, 200 μM, 300 μM, 500 μM, and 800 μM and the solution was stationary. At this time, the voltage increase rate and voltage decrease rate applied between the first electrode and the second electrode were each set to 20 mV / sec. In each of Examples 1 to 4, as shown in Figs. 3(A-1) to (A-4), a current peak was observed due to the interfacial migration of PFHxS- ions contained in the measurement target solution to the charge transfer liquid phase. In each of Examples 1 to 4, the PFHxF concentration dependence of the peak current value of the cyclic voltammograms shown in Figs. 3(A-1) to (A-4) was as shown in Fig. 3(B). 3(B) shows that when the concentration of PFHxS in the measurement solution is 200 μM or less, the peak current values are substantially the same in Examples 1 to 4. On the other hand, when the concentration of PFHxS in the measurement solution is 200 μM or more, the peak current value increases as the content of PEDOT-PEG:TFPB in the conductive polymer film increases.
[0025] The weight ratios of PEDOT-PEG:TFPB, AB, and PVDF contained in the conductive polymer film of the compound content analyzing cell according to Example 5 were 40%, 40%, and 20%, respectively.
[0026] Using the compound content analysis cell according to Example 5, the time profile of the current flowing between the first electrode and the second electrode was measured for each of the measurement target solutions containing 50 μM, 100 μM, 150 μM, and 200 μM of PFHxS. Here, the voltage applied between the first electrode and the second electrode was set to −0.35 V, and 0.5 μL of the measurement target solution was flowed in the flow path of the flow path member at a flow rate of 134 mm / min. As shown in FIG. 4, a tendency was observed in which the area of the time profile of the current value increases as the concentration of PFHxS increases. In addition, the electrolysis efficiency, which is the ratio of the measured value of the amount of electricity obtained by performing time integration on the time profile shown in FIG. 4 to the theoretical value of the amount of electricity calculated from the concentration and volume of the PHFxS solution put into the injector, was calculated, and it was equivalent to about 98% at all concentrations. From this, it was found that the electrolysis efficiency of PHFxS was calculated by the compound content analysis method according to the present invention described above. - It can be seen that the content can be measured with high accuracy.
[0027] The weight ratios of PEDOT-PEG:TFPB, AB, and PVDF contained in the conductive polymer film of the compound content analysis cell in Example 6 were 40%, 40%, and 20%, respectively.
[0028] Using the compound content analysis cell according to Example 6, a cyclic voltammogram was measured in a state where each of the measurement target solutions containing 50 μM of PFHxS was filled into the flow path of the flow path member and was left stationary. At this time, the voltage increase rate and voltage decrease rate of the voltage applied between the first electrode and the second electrode were each set to 20 mV / sec. In Example 6, as shown in FIG. 5(A), the PFHxS contained in the measurement target solution was - A current peak associated with the interfacial transfer of ions to the charge transfer liquid phase was observed around -0.25 V. This indicates that if the potential of the first electrode relative to the second electrode is more negative than -0.25 V, the PFHxS contained in the measurement solution is -It was found that interfacial migration of ions to the charge transfer liquid phase occurs. In addition, the time profile of the current value flowing between the first electrode and the second electrode of the measurement target solution containing 50 μM of PFHxS was measured using the compound content analysis cell according to Example 6. Here, the voltage applied between the first electrode and the second electrode was set to −0.35 V, and the flow rate of 0.5 μL of the measurement target solution flowing through the flow path of the flow path member was set to 134 mm / min. Then, the time profile was measured for each of the cases where the potential of the first electrode relative to the second electrode was set to −0.24 V, −0.245 V, −0.25 V, −0.3 V, and −0.35 V. As shown in FIG. 5(B), a difference in the time profile was observed between the case where the potential of the second electrode was higher than −0.25 V and the case where it was lower than −0.25 V. From this, it was found that the PFHxS contained in the measurement target solution was 0.01 μM. - It can be seen that the presence or absence of interfacial transfer of ions to the charge transfer liquid phase affects the time profile. In addition, the electrolysis efficiency, which is the ratio of the measured value of the quantity of electricity obtained by performing time integration on the time profile shown in FIG. 5(B) to the theoretical value of the quantity of electricity calculated from the concentration and volume of the PHFxS solution introduced into the injector, showed the dependency on the potential of the second electrode as shown in FIG. 6. As shown in FIG. 6, when the potential of the first electrode is set to a potential more negative than -0.3 V, the electrolysis efficiency is approximately 100%, whereas when the potential of the first electrode is set to -0.25 V or more, the theoretical value of the quantity of electricity is significantly reduced. From this, it can be seen that the content of PHFxS in the measurement target solution can be measured with high accuracy if the potential of the first electrode is set to a potential more negative than -0.3 V.
[0029] The weight ratios of PEDOT-PEG:TFPB, AB, and PVDF contained in the conductive polymer film of the compound content analysis cell in Example 7 were 40%, 40%, and 20%, respectively.
[0030] Using the compound content analysis cell according to Example 7, the time profile of the current flowing between the first electrode and the second electrode of the measurement target solution containing 50 μM of PFHxS was measured, and the flow rate dependency of the electrolysis efficiency was obtained based on the measured time profile. Here, the potential of the first electrode relative to the second electrode was set to −0.35 V. Then, the time profile of the current value was measured for each case in which the flow rate of 0.5 μL of the measurement target solution flowing through the flow path of the flow path member was changed. As shown in FIG. 7, it was found that the electrolysis efficiency was approximately 100% when the flow rate was 267 mm / min or less, whereas the electrolysis efficiency was significantly reduced when the flow rate was 300 mm / min or more. From this, it was found that, considering that the flow rate was 267 mm or less, i.e., the length of the flow path was 19 mm, the electrolysis efficiency was approximately 100% if the measurement target solution stayed in the flow path for 4.3 sec or more.
[0031] The weight ratios of PEDOT-PEG:TFPB, AB, and PVDF contained in the conductive polymer film of the compound content analysis cell according to Example 8 were 40%, 40%, and 20%, respectively.
[0032] Using the compound content analysis cell according to Example 8, the time profile of the current flowing between the first and second electrodes in the measurement target solution containing PFHxS was measured, and the concentration dependency of the electrolysis efficiency of PFHxS was obtained based on the measured time profile. Here, the voltage applied between the first and second electrodes was set to -0.35 V, and the flow rate of 0.5 μL of the measurement target solution flowing through the flow path of the flow path member was set to 134 mm / min, and the time profile of the current value was measured. As shown in Figs. 8(A) and (B), it was found that the electrolysis efficiency was approximately 100% when the concentration of PFHxS in the measurement target solution was in the range of 5 μM to 200 μM. In addition, as shown in Fig. 9, it was found that the theoretical value of the electric quantity calculated from the concentration and volume of the PHFxS solution injected into the injector and the electric quantity obtained by performing time integration on the time profile of the electric current value showed a high correlation when the concentration of PFHxS in the measurement target solution was in the range of 5 μM to 200 μM. From these findings, it can be seen that the PFHxs content in the measurement solution can be measured with high accuracy as long as the PFHxS concentration in the measurement solution is 5 μM or more and 200 μM or less.
[0033] The weight ratios of PEDOT-PEG:TFPB, AB, and PVDF contained in the conductive polymer film of the compound content analysis cell in Example 9 were 40%, 40%, and 20%, respectively.
[0034] Using the compound content analysis cell according to Example 9, a cyclic voltammogram was measured while each of the measurement target solutions containing 18.3 μM perfluorooctanesulfonic acid (PFOS) was filled into the flow path of the flow path member and left stationary. At this time, the voltage increase rate and voltage decrease rate applied between the first electrode and the second electrode were each set to 20 mV / sec. In Example 9, as shown in FIG. 10, the PFOS contained in the measurement target solution was - A current peak associated with the interfacial transfer of ions to the charge transfer liquid phase was observed around -0.12 V. From this, it can be seen that if the measurement target solution contains PFOS, and the potential of the first electrode relative to the second electrode is more negative than -0.12 V, the PFOS contained in the measurement target solution will be- It was found that interfacial migration of ions to the charge transfer liquid phase occurs. In addition, the time profile of the current value of the current flowing between the first electrode and the second electrode of the measurement target solution containing 18.3 μM of PFOS was measured using the compound content analysis cell according to Example 9. Here, the voltage applied between the first electrode and the second electrode was set to −0.35 V, the flow rate of 0.5 μL of the measurement target solution flowing in the flow path of the flow path member was set to 134 mm / min, and the potential of the first electrode relative to the second electrode was set to −0.35 V, and the time profile of the current value was measured. Then, the electrolysis efficiency was calculated based on the measured time profile. Here, the electrolysis efficiency was calculated based on the time profiles of the three current values obtained for the measurement target solution containing PFOS, and the electrolysis efficiency was 103% ± 1%. From this, it was found that the content of PFOS in the measurement target solution containing PFOS can be measured with high accuracy in the measurement target solution containing PFOS as well as in the measurement target solution containing PFHxS.
[0035] In addition, as the measurement target solution, one containing only PFOS having a linear structure and one containing both PFOS having a linear structure and PFOS of a branched isomer were prepared, and the above-mentioned electrolysis efficiency was measured for each. As a result, the electrolysis efficiency calculated based on the time profile of three current values obtained for the measurement target solution containing only PFOS having a linear structure was 102% ± 4%. On the other hand, the electrolysis efficiency calculated based on the time profile of three current values obtained for the measurement target solution containing both PFOS having a linear structure and PFOS of a branched isomer was 65% ± 9%. From this, it was found that the method according to Example 9 can selectively measure the content of PFOS having a linear structure in the measurement target solution. [Industrial Applicability]
[0036] The present invention is suitable as an apparatus for measuring the content of ionic surfactants such as PFAS. [Explanation of symbols]
[0037] 1: compound content analysis cell, 2: injector, 3: voltage source, 5: content calculation unit, 11: support member, 12: first electrode, 12a, 12b, 111a, 111b: through hole, 13: flow path member, 13a: flow path, 14: charge transfer liquid membrane, 15: conductive polymer membrane, 16: second electrode, 41: voltmeter, 42: ammeter, 111: first sub-support member, 112: second sub-support member, W: measurement target solution
Claims
1. A first electrode; a second electrode disposed opposite the first electrode; a flow path member that is sheet-like and penetrates in a thickness direction, and has a flow path formed therein in which a measurement target solution containing a measurement target compound ion is filled, and one surface side of the flow path in the thickness direction is covered with the first electrode; a charge transfer liquid film that contains a charge transfer liquid and covers the other surface side of the flow path in the thickness direction of the flow path member; a conductive polymer film that contains a conductive polymer and is interposed between the second electrode and the charge transfer liquid film; a content calculation unit that calculates a content of the compound ion of the measurement target contained in the measurement target solution by executing a time integration of a current value of a current flowing between the first electrode and the second electrode when a preset voltage is applied between the first electrode and the second electrode. Compound content analyzer.
2. The charge transfer liquid membrane contains 2-nitrophenyl octyl ether. The compound content analyzer according to claim 1 .
3. The conductive polymer membrane includes poly(3,4-ethylenedioxythiophene), bis-poly(ethylene glycol) doped with hydrophobic anions, acetylene carbon black, and polyvinylidene fluoride. The compound content analyzer according to claim 1 or 2.
4. The hydrophobic anion is any one of tetrakis[3,5-bis(trifluoromethyl)phenyl]borate, halogenated tetraphenylborate, and sulfonylimide. The compound content analyzer according to claim 3 .
5. The content of poly(3,4-ethylenedioxythiophene), bis-poly(ethylene glycol) to which tetrakis[3,5-bis(trifluoromethyl)phenyl]borate is added in the conductive polymer film is 5 wt % or more. The compound content analyzer according to claim 4.
6. The potential of the second electrode relative to the first electrode is more negative than −0.3 V. The compound content analyzer according to claim 1 or 2.
7. The concentration of the ion to be measured contained in the solution to be measured is 5 μM or more and 200 μM or less. The compound content analyzer according to claim 1 or 2.
8. a flow path member having a sheet-like flow path formed therein, the flow path being filled with a solution containing a compound ion of the target compound, the flow path member having one surface side of the flow path in the thickness direction covered with the first electrode; a charge transfer liquid membrane containing a charge transfer liquid and covering the other surface side of the flow path in the thickness direction of the flow path member; and a conductive polymer membrane containing a conductive polymer and interposed between the second electrode and the charge transfer liquid membrane, a step of calculating a content of the compound ion of the measurement target contained in the measurement target solution by performing a time integration of a current value of a current flowing between the first electrode and the second electrode when a preset voltage is applied between the first electrode and the second electrode, Compound content analysis method.
9. A first electrode; a second electrode disposed opposite the first electrode; a flow path member that is sheet-like and penetrates in a thickness direction, and has a flow path formed therein in which a measurement target solution containing a measurement target compound ion is filled, and one surface side of the flow path in the thickness direction is covered with the first electrode; a charge transfer liquid film that contains a charge transfer liquid and covers the other surface side of the flow path in the thickness direction of the flow path member; a conductive polymer film including a conductive polymer and interposed between the second electrode and the charge transfer liquid film; Cell for compound content analysis.
Citation Information
Patent Citations
Method for producing fluoropolymer powder
WO2020213691A1